PERFORMANCE ANALYSIS OF RANKINE CYCLE USING SUPERCRITICAL STEAM FOR ENERGY CONVERSION SYSTEM OF RDE - Ignatius Djoko Irianto (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2017)
PERFORMANCE ANALYSIS OF RANKINE CYCLE USING SUPERCRITICAL STEAM FOR ENERGY CONVERSION SYSTEM OF RDE. The energy conversion system in the experi- mental power reactor (RDE) is designed using a steam turbine or in a cogeneration configuration with a Rankine cycle. This energy conversion system also functions as a reactor coolant system that implements an indirect cycle. Between the primary cooling system and the secondary cooling system is mediated by a heat exchanger that acts as a steam generator (SG). The temperature of the reactor outlet is 700 oC and the temperature of the steam generator outlet is 530 oC with the pressure of 60 bar. One of the performance parameters for energy conversion systems is thermal efficiency. This research aims to study the possibility of increasing thermal efficiency by conditioning the supercriti- cal vapor in the turbine inlet. The analysis and calculation of cooling thermodynamic parameters and coolant system performance parameters are performed using ChemCAD computer software. A simu- lation using ChemCAD for the RDE energy conversion system by conditioning the supercritical va- por at various pressure variations obtained that the highest thermal efficiency of 29.41 % occurred at supercritical vapor conditions with a pressure of 270 bar. This thermal efficiency is about 2.5 % higher than thermal efficiency at a pressure of 60 bar. Therefore a pressure of 270 bar can be consi- dered as an operating parameter for the Rankine cycle on RDE. Keywords: experimental power reactor, cooling system, ChemCAD, thermal efficiency